Peran Badan Narkotika Nasional (BNN) Dalam Memberantas Penyalahgunaan Narkotika Di Kota Gorontalo - mohamad akbar paudie; Sumiyati Beddu; Suardi Rais (Fakultas Hukum Universitas Ichsan Gorontalo, 2025)
This study aims to: (1) How is the Role of the National Narcotics Agency (BNN) in Eradicating Drug Abuse in Gorontalo City, (2) Factors that Inhibit the Implementation of Rehabilitation of Drug Abuse Victims by the National Narcotics Agency (BNN) of Gorontalo City. The type of research used in this study is a research on reality rules. Empirical research is research with field data as the primary data source, such as interview output and observation. Empirical research is used to analyze rules that are considered to be the behavior of people who always interact and have social aspects. The results of this study indicate that: (1) To determine the Role of the National Narcotics Agency (BNN) in the implementation of Drug Abuse Rehabilitation in Gorontalo City, (2) Factors Inhibiting the Role of the Police in North Bolaang Mongondow are Budget limitations, Low community participation, Lack of facilities and infrastructure. The author's suggestions in this study: (1). To the police to be more serious in eradicating drug abuse in North Bolaang Mongondow (2). To find out the factors that hinder the implementation of the rehabilitation of victims of drug abuse by the National Narcotics Agency (BNN) of Gorontalo City.